2017
DOI: 10.1111/jam.13483
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic expression of functional Fab fragments in Escherichia coli using a novel combination of dual SUMO expression cassette and EnBase® cultivation mode

Abstract: The presented strategy provides not only a novel method to produce soluble and active form of an anti-VEGF Fab but also may use in the efficient production of other antibody fragments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…Furthermore, hydrophobic reactions that make inclusion bodies and aggregation of the recombinant proteins happen less (Krause et al, 2010) and for this reason a higher soluble form of α-luffin was achieved at 30 °C and 25 °C in comparison to 37 °C. On the other hand, the chaperone-like manner of SUMO tag and high activity of chaperones at 30 °C can improve the solubility rate of α-luffin (Rezaie et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hydrophobic reactions that make inclusion bodies and aggregation of the recombinant proteins happen less (Krause et al, 2010) and for this reason a higher soluble form of α-luffin was achieved at 30 °C and 25 °C in comparison to 37 °C. On the other hand, the chaperone-like manner of SUMO tag and high activity of chaperones at 30 °C can improve the solubility rate of α-luffin (Rezaie et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Considering our protein characteristics besides EnBase system special features, 30 and 25 °C temperatures were studied. The 30 °C was chosen based on recommended EnBase protocol due to higher oxygen solubility and reduced evaporation while studying usual nontoxic proteins expression ( 25 , 43 ). Here also, this temperature resulted in higher specific production of total protein in both batch and fed-batch method ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In the Studier's autoinduction medium [84], the growth is supported at the beginning by glucose, and when glucose is exhausted protein expression is autoinduced by a diauxic shift to lactose utilization, while glycerol is also coutilized as a major carbon source during expression. The most recent EnBase ® medium (EnPresso, GmbH, Berlin, Germany), in which glucose, as a primary carbon source, is gradually provided from a soluble polysaccharide by biocatalytic degradation [85], has been successfully used for high-yield cytoplasmic and periplasmic expression of several proteins including antibody fragments [86][87][88][89]. Several studies have demonstrated that the yield of recombinant antibody fragments in E. coli significantly improves at growth temperature below 30 • C, likely due to the reduction of translation rate that favors proper Ig-like folding and reduces aggregation [90][91][92].…”
Section: Overcoming Drawbacks In Small-scale Productionsmentioning
confidence: 99%
“…Several reports have also suggested that the use of fusion partners such as GST [118], maltose-binding protein (MBP) [119,120], small ubiquitin-related modifier (SUMO) [87,121] and thioredoxin (Trx) [122] to the target proteins, especially to scFv fragments, results in solubility-enhancing properties and in increased yields of soluble and active products. However, the fusion partners must be cleaved as big tags usually interfere with the folding of the target protein and with its activity.…”
Section: Cytoplasmic Expressionmentioning
confidence: 99%
See 1 more Smart Citation